Sustainable Modular Adaptive Redundancy Technique Emphasizing Partial Reconfiguration for Reduced Power Consumption. (25th August 2011) - Al-Haddad, R.; Oreifej, R.; Ashraf, R. A.; DeMara, R. F.
Abstract : As reconfigurable devices' capacities and the complexity of applications that use them increase, the need for self-reliance of deployed systems becomes increasingly prominent. Organic computing paradigms have been proposed for fault-tolerant systems because they promote behaviors that allow complex digital systems to adapt and survive in demanding environments. In this paper, we develop a sustainable modular adaptive redundancy technique (SMART) composed of a two-layered organic system. The hardware layer is implemented on a Xilinx Virtex-4 Field Programmable Gate Array (FPGA) to provide self-repair using a novel approach called reconfigurable adaptive redundancy system (RARS) . The software layer supervises the organic activities on the FPGA and extends the self-healing capabilities through application-independent, intrinsic, and evolutionary repair techniques that leverage the benefits of dynamic partial reconfiguration (PR). SMART was evaluated using a Sobel edge-detection application and was shown to tolerate stressful sequences of injected transient and permanent faults while reducing dynamic power consumption by 30% compared to conventional triple modular redundancy (TMR) techniques, with nominal impact on the fault-tolerance capabilities. Moreover, PR is employed to keep the system on line while under repair and also to reduce repair time. Experiments have shown a 27.48% decrease in repair time when PR is employed compared to the full bitstream configuration case.